Penyusunan Instrumen Penilaian Afektif di Sekolah - Ayu Riana Meyliasari (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to examine the concept of affective assessment, the steps in developing affective assessment instruments, and the challenges and solutions that may be encountered in developing such instruments. Through a literature review, this study analyzes various sources related to affective assessment. The results of the study show that affective assessment plays a significant role in measuring students' holistic development, but it is often overlooked. The affective domain encompasses various aspects such as attitudes, values, interests, and emotions. The development of affective assessment instruments requires careful planning, from determining indicators to data analysis. Challenges in developing these instruments include a lack of teacher understanding, limited availability of valid and reliable instruments, and difficulties in producing objective assessments. This study concludes that the development of high-quality affective assessment instruments is essential for improving the quality of learning and a more comprehensive understanding of student development.